Pengaruh Keterampilan Kewirausahaan dan Pengalaman Terhadap Keberhasilan Usaha Barbershop di Kecamatan Medan Sunggal - Gultom, Chrisdahner Edoardo; Putra, Irwansyah; Darmansyah, Muthya Rahmi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine “The Effect of Entrepreneurial Skills and Experience on Barbershop Business Success in Medan Sunggal District”. Where entrepreneurial skills are success in practicing the abilities acquired by an entrepreneur in terms of applying knowledge and good personal qualities to carry out entrepreneurial activities, experience is the knowledge that entrepreneurs have gained through a series of business activities that have been carried out, while business success is a situation where a business is at a better point than the previous situation and in that position the business has been able to achieve the expected goals. This study adopts a causal associative quantitative research type. The data used in this study is primary data so that data collection is done by distributing research questionnaires to 35 Barbershop businesses in Medan Sunggal District using saturated sampling techniques. Based on the results of the partial test (t test) it is concluded that partially entrepreneurial skills have a positive and significant effect on business success and partially experience has a positive and significant effect on business success. Based on the results of the simultaneous test (F test) it is concluded that simultaneously entrepreneurial skills and experience simultaneously have a positive and significant effect on the success of the Barbershop business in Medan Sunggal District. In the coefficient of determination (R2) test, it can be seen that the Adjusted R Square value is 0.592. Thus describing that the value of the variance owned by the business success of the entrepreneurial skills and experience variables is 59.2% and the remaining 40.8% is influenced by other variables or factors not examined and not explained in this study.